A narrative review of ambulatory care education in Canadian internal medicine (Canadian Medical Education Journal, 2020)
Background: The Canadian healthcare system faces increasing patient volumes and complexity amidst funding constraints. Ambulatory care offers a potential solution to some of these challenges. Despite growing emphasis on the provision of ambulatory care, there has been a relative paucity of ambulatory care training curricula within Canadian internal medicine residency programs. We conducted a narrative review to understand the current state of knowledge on postgraduate ambulatory care education (ACE), in order to frame a research agenda for Canadian Internal Medicine ACE.Methods: We searched OVID Medline, Embase, and PsycINFO for articles that included the concepts of ambulatory care and medical or health professions education from 2005-2015. After sorting for inclusion/exclusion, we analyzed 30 articles, looking for dominant claims about ACE in Internal Medicine literature.Results: We found three claims. First, ACE is considered to be a necessary component of medical training because of its distinction from inpatient learning environments. Second, current models of ambulatory care clinics do not meet residency education needs. Third, ACE presents opportunities to develop non-medical expert roles. Conclusions: The findings of our narrative review highlight a need for additional research regarding ACE in Canada to inform optimal ambulatory internal medicine training structures and alignment of educational and societal needs.